Rapid enhancement of brush border glucose uptake after exposure of rat jejunal mucosa to glucose. Issue 4 (October 1996) - Sharp, P A; Debnam, E S; Srai, S K
Abstract : BACKGROUND: Increased jejunal glucose transport after ingestion of carbohydrate rich diets may reflect higher concentrations of lumenal glucose. Normal processing of carbohydrate causes wide fluctuations in glucose concentration in the jejunal lumen and this raises the question of whether the high lumenal concentrations seen at peak digestion affect glucose uptake. AIMS: To study the effects of 30 minute exposure of rat jejunal mucosa to glucose on sodium-glucose transporter (SGLT1) mediated glucose transport across the brush border membrane. METHODS: Jejunal mucosa was exposed in vitro or in vivo to 25 mM glucose or 25 mM mannitol for 30 minutes. In addition, isolated villus enterocytes were incubated with mannitol or glucose for the same time. Brush border membrane vesicles were isolated from these preparations and phlorizin sensitive 3H-D-glucose accumulation was measured. RESULTS: Lumenal glucose in vivo significantly enhanced SGLT1 mediated glucose uptake by 49.2-57.2%. For jejunal loops in vitro, the increase was 32.0-85.2%. Kinetic analysis disclosed a 50% greater Vmax for glucose uptake in each preparation. The facilitated and passive components of uptake were, however, unaffected by prior exposure to glucose. Incubation of villus enterocytes with 25 mM glucose did not influence glucose uptake by brush border membranes. Finally, exposure of intact mucosa to 20 mM galactose, a nonmetabolised sugar also transported by SGLT1, did not alter glucose transport. CONCLUSIONS: Lumenal glucose promotes glucose transport by brush border membrane within 30 minutes. An intact mucosa is necessary for upregulation and evidence suggests that the response is mediated by locally acting mechanisms.